Plate glass based on diffusivity strengthening and preparation method thereof
By mixing and melting broken glass with other raw materials in a certain proportion, annealing and strengthening treatment, a flat glass with diffusion reinforcement was prepared, which solved the problem of low utilization rate of broken glass for traditional flat glass and improved resource utilization and Product performance.
Patent Information
- Application Number
- CN202411428626.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-07
AI Technical Summary
Traditional flat glass has a low utilization rate of broken glass during production, resulting in a low resource utilization rate.
By mixing and melting broken glass with sand, sodium carbonate, limestone, zinc oxide, titanium dioxide, bauxite, alumina, barium sulfate, magnesium oxide and other raw materials in a certain proportion, forming a glass liquid, and annealing and strengthening treatment , a flat glass with diffusivity reinforcement was prepared.
It significantly improves the utilization rate of broken glass, reduces raw material consumption and waste emissions, improves resource utilization, and adjusts the raw material portion according to different needs to meet the needs of different consumers.
Smart Images

Figure CN119390351A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flat glass, in particular to flat glass based on diffusion strengthening and a preparation method thereof. Background Art
[0002] Flat glass is an inorganic glass product, usually in plate form, mainly composed of sodium calcium silicate. It has a variety of properties, including light transmission, transparency, heat preservation, sound insulation, wear resistance and climate change resistance. Flat glass is widely used in many fields such as building decoration engineering, transportation manufacturing and interior decoration due to its excellent performance. Its main forming methods include float glass, groove vertical drawing method, grooveless vertical drawing method, rolling method, flat drawing method, etc. In addition, flat glass can also be colored, surface treated, polished, enhanced, glazed, composited and other treatments as needed to make glass products of different colors or with various special properties.
[0003] When using flat glass, it may break due to accidents. Traditional flat glass is usually prepared with sand, sodium carbonate, limestone and other raw materials, and its utilization rate of broken glass is low, resulting in low resource utilization rate of traditional flat glass in production. Therefore, flat glass based on diffusion strengthening and its preparation method are proposed to solve the above problems. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides a flat glass based on diffusion strengthening and a preparation method thereof, which solves the problem that the utilization rate of broken glass in traditional flat glass is low, resulting in low resource utilization rate in the production of traditional flat glass.
[0005] To achieve the above objectives, the present invention is implemented through the following technical scheme: the flat glass based on diffusion strengthening includes the following raw materials in parts by weight: 50-80 parts of broken glass, 30-60 parts of sand, 10-20 parts of sodium carbonate, 5-10 parts of limestone, 1-5 parts of zinc oxide, 1-5 parts of titanium dioxide, 1-3 parts of bauxite, 1-3 parts of aluminum oxide, 1-3 parts of barium sulfate, and 1-3 parts of magnesium oxide.
[0006] Preferably, the particle size of the cullet is 0.1 mm-3 mm.
[0007] A method for preparing flat glass based on diffusion strengthening comprises the following steps:
[0008] S1. Raw material preparation: clean the collected broken glass to remove dust, oil and impurities, then grind it through a grinder, and then sieve it to obtain broken glass raw materials with a particle size of 0.1mm-3mm;
[0009] S2. Raw material mixing: the broken glass raw material is uniformly mixed with sand, sodium carbonate, limestone, zinc oxide, titanium dioxide, bauxite, aluminum oxide, barium sulfate and magnesium oxide through an air flow mixer;
[0010] S3, melting raw materials: putting the mixed raw materials into a high temperature furnace to obtain glass liquid;
[0011] S4, forming process: discharging the glass liquid into a molten tin pool to uniformly form the glass liquid, thereby obtaining glass;
[0012] S5, annealing treatment: placing the glass in an annealing furnace and controlling the temperature uniformly to make the temperature of the glass reach 20°C-25°C;
[0013] S6. Strengthening treatment: immerse the annealed glass in a high concentration potassium salt solution to replace the sodium ions on its surface with potassium ions. After the replacement is completed, immerse it in a lithium salt solution to replace the potassium ions on its surface with lithium ions. After the replacement is completed, take out the glass and clean the excess salt on its surface to obtain diffusion-strengthened flat glass.
[0014] Preferably, the mixing time in step S2 is 15 minutes to 30 minutes.
[0015] Preferably, in step S3, the temperature of the high temperature furnace is 1400° C.-1600° C., and the time is 2 hours-4 hours.
[0016] Preferably, in step S4, the temperature of the glass liquid is 1400° C.-1600° C., the temperature of the glass is 600° C.-700° C., and the thickness is 4 mm-15 mm.
[0017] Preferably, in step S5, the temperature of the glass is 600°C-700°C, the cooling rate of the annealing furnace is 10°C-30°C per hour, a nitrogen supply system is provided in the annealing furnace, and the nitrogen concentration in the annealing furnace is 95%-99.9%.
[0018] Preferably, the concentration of the high concentration potassium salt solution in step S6 is 25%-50% KCl, and the concentration of the lithium salt solution is 10%-30% Li 2 CO 3 , the soaking time is 30 minutes to 5 hours.
[0019] Preferably, the nitrogen supply system includes a nitrogen source module for generating corresponding nitrogen; a delivery module for delivering nitrogen into the annealing furnace and controlling the delivery flow rate; and a monitoring module for monitoring the concentration and pressure of nitrogen in the annealing furnace.
[0020] The present invention provides a flat glass based on diffusion strengthening and a preparation method thereof, which has the following beneficial effects:
[0021] 1. The present invention uses a certain amount of broken glass as one of the raw materials of diffusion-strengthened flat glass, and prepares it with sand, sodium carbonate, limestone, zinc oxide, titanium dioxide, bauxite, aluminum oxide, barium sulfate, and magnesium oxide in a certain proportion, thereby enhancing the utilization rate of broken glass and reducing the waste of resources, thereby significantly reducing raw material consumption and waste emissions, and improving resource utilization, thereby solving the problem that the utilization rate of broken glass is low in traditional flat glass, resulting in low resource utilization in the production of traditional flat glass.
[0022] 2. The present invention can change the compressive strength, ultraviolet transmittance and thermal conductivity of flat glass by increasing or decreasing the amount of each raw material within a reasonable range, so that the amount can be adjusted according to different needs to meet the various needs of different consumers, thereby enhancing practicality.
[0023] 3. The present invention anneals the glass through an annealing furnace, and provides nitrogen through a nitrogen supply system inside the annealing furnace, thereby reducing oxidation and discoloration of the glass during annealing, ensuring the color and transparency of the glass, and relieving internal stress, thereby improving mechanical properties and thermal stability, so that better quality assurance is obtained during glass preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the method for preparing flat glass based on diffusion strengthening of the present invention; DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] An embodiment of the present invention provides a flat glass based on diffusion strengthening, comprising the following raw materials in parts by weight: 50-80 parts of cullet, 30-60 parts of sand, 10-20 parts of sodium carbonate, 5-10 parts of limestone, 1-5 parts of zinc oxide, 1-5 parts of titanium dioxide, 1-3 parts of bauxite, 1-3 parts of aluminum oxide, 1-3 parts of barium sulfate, and 1-3 parts of magnesium oxide; the particle size of the cullet is 0.1 mm-3 mm.
[0027] Specifically, the addition of broken glass can significantly reduce the consumption of raw materials and waste emissions, improve resource utilization, and improve the toughness, transparency and chemical resistance of glass; sand provides silicon dioxide to enhance the structural stability of glass and ensure the transparency and heat resistance of finished products; the addition of sodium carbonate can reduce the melting temperature of glass, improve the melting efficiency, and improve the fluidity and molding performance of glass, thereby making the molding process smoother; limestone provides calcium oxide to improve the chemical stability and water resistance of glass, make glass more wear-resistant and extend its service life; the addition of zinc oxide can improve the optical properties of glass, improve its UV resistance, and enhance the color and gloss of glass, increasing its aesthetics; the addition of titanium dioxide can improve the strength and wear resistance of glass, while further increasing The anti-ultraviolet ability of glass improves color saturation; the provision of alumina by bauxite helps to enhance the hardness and heat resistance of glass, and improves the corrosion resistance and high temperature resistance of glass; the addition of alumina improves the chemical resistance and mechanical strength of glass, thereby enhancing the toughness and heat resistance of glass and reducing the thermal expansion coefficient; the addition of barium sulfate improves the optical properties of glass and increases its density, thereby improving the transparency and color depth of glass, while increasing its anti-ultraviolet ability; the addition of magnesium oxide improves the heat resistance and chemical stability of glass, thereby enhancing the strength and wear resistance of glass, and helps to improve the performance of finished products; thereby enhancing the utilization rate of broken glass and reducing the waste of resources, thereby solving the problem of low utilization rate of broken glass by traditional flat glass, which leads to low resource utilization rate of traditional flat glass during production.
[0028] Please refer to the attached Figure 1 , a method for preparing flat glass based on diffusion strengthening, comprising the following steps:
[0029] S1. Raw material preparation: clean the collected broken glass to remove dust, oil and impurities, then grind it through a grinder, and then sieve it to obtain broken glass raw materials with a particle size of 0.1mm-3mm;
[0030] Specifically, the collected broken glass is cleaned to remove dust, oil and impurities, then ground by a grinder, and then sieved to obtain broken glass raw materials with a particle size of 0.1mm-3mm, so that the uniformity of the broken glass can be improved in the subsequent mixing and melting process.
[0031] S2. Raw material mixing: the broken glass raw material is uniformly mixed with sand, sodium carbonate, limestone, zinc oxide, titanium dioxide, bauxite, aluminum oxide, barium sulfate and magnesium oxide through an air flow mixer;
[0032] Specifically, the broken glass raw materials are uniformly mixed with sand, sodium carbonate, limestone, zinc oxide, titanium dioxide, bauxite, aluminum oxide, barium sulfate, and magnesium oxide through an air flow mixer, so that all the raw materials can be uniformly mixed to ensure the best effect of each component and improve the physical and chemical properties of the glass.
[0033] S3, melting raw materials: putting the mixed raw materials into a high temperature furnace to obtain glass liquid;
[0034] Specifically, the glass liquid is prepared by placing the mixed raw materials into a high-temperature furnace, thereby ensuring that the raw materials are fully melted to form high-quality glass liquid, and the control of the melting time also helps to reduce defects such as bubbles.
[0035] S4, forming process: discharging the glass liquid into a molten tin pool to uniformly form the glass liquid, thereby obtaining glass;
[0036] Specifically, the glass liquid is discharged into a molten tin pool to be uniformly shaped to obtain glass, thereby ensuring the fluidity of the glass liquid and obtaining a glass sheet with a smooth surface and uniform thickness.
[0037] S5, annealing treatment: placing the glass in an annealing furnace and controlling the temperature uniformly to make the temperature of the glass reach 20°C-25°C;
[0038] Specifically, by placing the glass in an annealing furnace and performing uniform temperature control to make the temperature of the glass reach 20°C-25°C, the stress in the glass can be eliminated and the stability of the glass can be ensured. The use of nitrogen can reduce oxidation and discoloration of the glass, ensure the color and transparency of the glass, and internal stress can be relieved, thereby improving mechanical properties and thermal stability.
[0039] S6. Strengthening treatment: immerse the annealed glass in a high concentration potassium salt solution to replace the sodium ions on its surface with potassium ions. After the replacement is completed, immerse it in a lithium salt solution to replace the potassium ions on its surface with lithium ions. After the replacement is completed, take out the glass and clean the excess salt on its surface to obtain diffusion-strengthened flat glass.
[0040] Specifically, the annealed glass is immersed in a high-concentration potassium salt solution to replace the sodium ions on its surface with potassium ions. After the replacement is completed, it is immersed in a lithium salt solution to replace the potassium ions on its surface with lithium ions. After the replacement is completed, the glass is taken out and the excess salt on its surface is cleaned to obtain diffusion-strengthened flat glass, which can increase the strength and heat resistance of the glass surface and significantly improve its compressive strength.
[0041] The mixing time in step S2 is 15 minutes to 30 minutes; the temperature of the high-temperature furnace in step S3 is 1400°C to 1600°C, and the time is 2 hours to 4 hours; the temperature of the glass liquid in step S4 is 1400°C to 1600°C, the temperature of the glass is 600°C to 700°C, and the thickness is 4mm to 15mm; the temperature of the glass in step S5 is 600°C to 700°C, the cooling rate of the annealing furnace is 10°C to 30°C per hour, and a nitrogen supply system is provided in the annealing furnace, and the nitrogen concentration in the annealing furnace is 95% to 99.9%; the concentration of the high-concentration potassium salt solution in step S6 is 25% to 50% KCl, and the concentration of the lithium salt solution is 10% to 30% Li 2 CO 3 The immersion time is 30 minutes to 5 hours; the nitrogen supply system includes a nitrogen source module for generating corresponding nitrogen; a delivery module for delivering nitrogen to the annealing furnace and controlling the delivery flow; and a monitoring module for monitoring the concentration and pressure of nitrogen in the annealing furnace.
[0042] The following is further introduced in conjunction with specific embodiments:
[0043] Embodiment 1:
[0044] The flat glass based on diffusion strengthening includes the following raw materials in parts by weight: 50 parts of cullet, 30 parts of sand, 10 parts of sodium carbonate, 5 parts of limestone, 1 part of zinc oxide, 1 part of titanium dioxide, 1 part of bauxite, 1 part of aluminum oxide, 1 part of barium sulfate, and 1 part of magnesium oxide; the particle size of the cullet is 2 mm.
[0045] A method for preparing flat glass based on diffusion strengthening comprises the following steps:
[0046] S1. Raw material preparation: clean the collected broken glass to remove dust, oil and impurities, then grind it through a grinder, and then sieve it to obtain broken glass raw materials with a particle size of 2 mm;
[0047] S2. Raw material mixing: the broken glass raw material is uniformly mixed with sand, sodium carbonate, limestone, zinc oxide, titanium dioxide, bauxite, aluminum oxide, barium sulfate and magnesium oxide through an air flow mixer;
[0048] S3, melting raw materials: putting the mixed raw materials into a high temperature furnace to obtain glass liquid;
[0049] S4, forming process: discharging the glass liquid into a molten tin pool to uniformly form the glass liquid, thereby obtaining glass;
[0050] S5, annealing treatment: placing the glass in an annealing furnace and controlling the temperature uniformly to make the temperature of the glass reach 20°C;
[0051] S6. Strengthening treatment: immerse the annealed glass in a high concentration potassium salt solution to replace the sodium ions on its surface with potassium ions. After the replacement is completed, immerse it in a lithium salt solution to replace the potassium ions on its surface with lithium ions. After the replacement is completed, take out the glass and clean the excess salt on its surface to obtain diffusion-strengthened flat glass.
[0052] The mixing time in step S2 was 30 minutes.
[0053] In step S3, the temperature of the high temperature furnace is 1600° C. and the time is 3 hours.
[0054] In step S4, the temperature of the glass liquid is 1500° C., the temperature of the glass is 650° C., and the thickness is 9 mm.
[0055] In step S5, the temperature of the glass is 650° C., the cooling rate of the annealing furnace is 20° C. per hour, a nitrogen supply system is provided in the annealing furnace, and the nitrogen concentration in the annealing furnace is 99.9%.
[0056] In step S6, the concentration of the high concentration potassium salt solution is 50% KCl, and the concentration of the lithium salt solution is 30% Li 2 CO 3 , the soaking time is 3 hours.
[0057] Embodiment 2:
[0058] The difference between this embodiment and the above-mentioned embodiment 1 is that:
[0059] The diffusion-strengthened flat glass comprises the following raw materials in parts by weight: 80 parts of cullet, 60 parts of sand, 20 parts of sodium carbonate, 10 parts of limestone, 5 parts of zinc oxide, 5 parts of titanium dioxide, 3 parts of bauxite, 3 parts of aluminum oxide, 3 parts of barium sulfate, and 3 parts of magnesium oxide.
[0060] Embodiment 3:
[0061] The difference between this embodiment and the above-mentioned embodiment 1 is that:
[0062] The diffusion-strengthened flat glass comprises the following raw materials in parts by weight: 65 parts of cullet, 45 parts of sand, 15 parts of sodium carbonate, 8 parts of limestone, 3 parts of zinc oxide, 3 parts of titanium dioxide, 2 parts of bauxite, 2 parts of aluminum oxide, 2 parts of barium sulfate, and 2 parts of magnesium oxide.
[0063] Table 1:
[0064] contrast Example 1 Example 2 Example 3 Standard value Compressive strength(MPa) 100 110 120 95 UV transmittance 4% 2% 3% 80% Thermal conductivity (W / m·K) 1 0.8 0.9 1.25
[0065] The comparison in the above table is for flat glass. It can be seen from Table 1 that adding different amounts of cullet can affect the compressive strength value of flat glass, and further affect the utilization rate of cullet in the preparation of flat glass. Among them, different amounts of sand, sodium carbonate, limestone, zinc oxide, titanium dioxide, bauxite, aluminum oxide, barium sulfate, and magnesium oxide can affect the compressive strength, ultraviolet transmittance, and thermal conductivity value of flat glass, and further affect the utilization efficiency of cullet in flat glass, thereby affecting the utilization rate of resources.
[0066] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Flat glass based on diffusion strengthening, characterized in that: The invention comprises the following raw materials in parts by weight: 50-80 parts of broken glass, 30-60 parts of sand, 10-20 parts of sodium carbonate, 5-10 parts of limestone, 1-5 parts of zinc oxide, 1-5 parts of titanium dioxide, 1-3 parts of bauxite, 1-3 parts of aluminum oxide, 1-3 parts of barium sulfate and 1-3 parts of magnesium oxide.
2. The diffusion-strengthened flat glass according to claim 1, characterized in that: The particle size of the cullet is 0.1 mm to 3 mm.
3. A method for preparing flat glass based on diffusion strengthening, characterized in that: The diffusion-strengthened flat glass according to claim 1 or 2 comprises the following steps: S1. Raw material preparation: clean the collected broken glass to remove dust, oil and impurities, then grind it through a grinder, and then sieve it to obtain broken glass raw materials with a particle size of 0.1mm-3mm; S2. Raw material mixing: the broken glass raw material is uniformly mixed with sand, sodium carbonate, limestone, zinc oxide, titanium dioxide, bauxite, aluminum oxide, barium sulfate and magnesium oxide according to the proportion through an air flow mixer; S3, melting raw materials: putting the mixed raw materials into a high temperature furnace to obtain glass liquid; S4, forming process: discharging the glass liquid into a molten tin pool to uniformly form the glass liquid, thereby obtaining glass; S5, annealing treatment: placing the glass in an annealing furnace and controlling the temperature uniformly to make the temperature of the glass reach 20°C-25°C; S6. Strengthening treatment: immerse the annealed glass in a high concentration potassium salt solution to replace the sodium ions on its surface with potassium ions. After the replacement is completed, immerse it in a lithium salt solution to replace the potassium ions on its surface with lithium ions. After the replacement is completed, take out the glass and clean the excess salt on its surface to obtain diffusion-strengthened flat glass.
4. The method for preparing flat glass based on diffusion strengthening according to claim 3, characterized in that: The mixing time in step S2 is 15 minutes to 30 minutes.
5. The method for preparing flat glass based on diffusion strengthening according to claim 3, characterized in that: In step S3, the temperature of the high temperature furnace is 1400° C.-1600° C., and the time is 2 hours-4 hours.
6. The method for preparing flat glass based on diffusion strengthening according to claim 3, characterized in that: In step S4, the temperature of the glass liquid is 1400° C.-1600° C., the temperature of the glass is 600° C.-700° C., and the thickness is 4 mm-15 mm.
7. The method for preparing flat glass based on diffusion strengthening according to claim 3, characterized in that: In step S5, the temperature of the glass is 600°C-700°C, the cooling rate of the annealing furnace is 10°C-30°C per hour, a nitrogen supply system is provided in the annealing furnace, and the nitrogen concentration in the annealing furnace is 95%-99.9%.
8. The method for preparing flat glass based on diffusion strengthening according to claim 3, characterized in that: The concentration of the high concentration potassium salt solution in step S6 is 25%-50% KCl, and the concentration of the lithium salt solution is 10%-30% Li 2 CO 3 , the soaking time is 30 minutes to 5 hours.
9. The method for preparing flat glass based on diffusion strengthening according to claim 7, characterized in that: The nitrogen supply system includes a nitrogen source module for generating corresponding nitrogen; a delivery module for delivering nitrogen into the annealing furnace and controlling the delivery flow; and a monitoring module for monitoring the concentration and pressure of nitrogen in the annealing furnace.